Local Language Barriers in pronouncing English words: A Case study among Mandailingnese students - Siregar, Ayu Meita Puteri (ELITE JOURNAL, 2024)
This study addresses the challenges faced by Mandailingnese students in pronouncing English words. The interference of the Mandailing language in English poses several difficulties for these students. Therefore, this study aims to identify the specific problems encountered by Mandailing students. Conducted at STAIN Mandailing Natal in the Family Law Study Program, this research adopts a qualitative research design with a case study approach. The instruments utilized include an oral test involving the reading of three different texts, supported by audio recordings, and interviews to explore students' pronunciation challenges in English. The researchers identified various issues affecting Mandailing students' pronunciation, including linguistic interference from the Mandailing language, misconceptions, lack of motivation to study, environmental factors, ineffective study habits, limited access to modern technology, economic constraints, and a lack of awareness regarding the importance of English language proficiency. From these findings, it can be inferred that Mandailing students encounter numerous hurdles in pronouncing English words, leading to decreased confidence and interest in the language. Therefore, educators and institutions are urged to address these challenges to support Mandailing students effectively.